A rapid, simple and ultrasensitive spectrofluorimetric method for the direct detection of metformin in real samples based on a nanoquenching approach. (2nd December 2020) - Azarian, Sina; Shaghaghi, Masoomeh; Dehghan, Gholamreza; Sheibani, Nader
Abstract: Metformin (MET), as an oral antidiabetic and antihyperglycemic agent, is widely used to treat type II diabetes mellitus. Because of its increasing consumption, developing a fast, simple, and selective method to determine its concentration in biological samples (serum and urine) and pharmaceutical formulations (tablets) is of great interest. In this study, we used a FRET‐based fluorescent nanosensor (Tb–phen–AgNPs system) for sensitive detection of MET in tablet and serum samples. This method is based on the enhancing effect of MET on the emission intensity of the Tb–phen complex, which is quenched by AgNPs via energy transfer process (turn off–on mode). A good linear relationship between the MET concentration and enhanced emission intensity of the Tb–phen–AgNPs system was observed in the range of (0.75–3.7) × 10 −6 M under optimum conditions. Limit of detection and limit of quantitation were calculated to be 0.43 × 10 −6 M and 1.31 × 10 −6 M, respectively. This method was successfully used to determine MET concentrations in pharmaceutical dosage form and in spiked serum sample. The obtained recoveries from pharmaceutical formulation and serum sample were in the range 86.75–98.97% and 85.10–100.96%, respectively. Collectively, our results indicated that the method described here is simple, sensitive, cost effective, and free from interference. Therefore, it can be used as an effective and routine method for the direct and rapid determination of MET levels in biological samples such as serum. Abstract : Metformin gradually restores the emission intensity of Tb–phen‐complex quenched with AgNps. A rapid and sensitive approach for the detection of Metformin.